2021
DOI: 10.1039/d1cy00588j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient depolymerization of lignins to alkylphenols using phosphided NiMo catalysts

Abstract: Greening up the chemical industry by using waste biomass streams as feed is a topic of high relevance. Residual lignins from for example the pulp and paper industry and second-generation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Such aromatic chemicals can be obtained by acid- and base-catalyzed depolymerization approaches, oxidation, and catalytic hydrotreatment . Such hydrotreatments are typically performed using a supported metal catalyst in combination with a hydrogen source (e.g., molecular hydrogen) in the presence (e.g., dodecane, dioxane, alcohols, and water) and absence of solvents. In the latter case, the lignin or products thereof act as the solvent and this is considered advantageous from a technoeconomic point of view. The lignin oils may either serve as a source for biobased chemicals like alkylphenols, or, after deep hydrotreatment, a biofuel with properties mimicking current hydrocarbon fuels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such aromatic chemicals can be obtained by acid- and base-catalyzed depolymerization approaches, oxidation, and catalytic hydrotreatment . Such hydrotreatments are typically performed using a supported metal catalyst in combination with a hydrogen source (e.g., molecular hydrogen) in the presence (e.g., dodecane, dioxane, alcohols, and water) and absence of solvents. In the latter case, the lignin or products thereof act as the solvent and this is considered advantageous from a technoeconomic point of view. The lignin oils may either serve as a source for biobased chemicals like alkylphenols, or, after deep hydrotreatment, a biofuel with properties mimicking current hydrocarbon fuels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to noble metal catalysts, limonite ore, a low-cost Fe-containing catalyst, was used for the hydrotreatment of Alcell lignin, yielding 19.0 wt % monomers and 8.7 wt % alkylphenols based on lignin intake (450 °C, 100 bar initial H 2 pressure, and 4 h reaction time) . Recently, it was found that Ni catalysts also have potential and, for instance, it was shown that the use of a phosphided bimetallic NiMo catalyst (NiMoP/SiO 2 ) results in a lignin oil yield with 34.4 wt % monomers of which half were alkylphenols (400 °C, 100 bar initial H 2 pressure, and 2 h reaction time with 10 wt % catalyst loading) …”
Section: Introductionmentioning
confidence: 99%
“…Catalytic hydrotreatment of unmilled and milled lignins was conducted in a batch reactor at 400 °C for 2 h and 100 bar initial H 2 pressure without an external solvent, using a NiMoP/SiO 2 catalyst (the detailed characterization of the NiMoP/SiO 2 catalyst is presented in the Supporting Information). Typically, the hydrotreatment led to the formation of gas-phase products and a liquid phase with suspended solids. The latter was separated by centrifugation followed by acetone extraction to obtain an organic product oil, an aqueous phase, and a solid residue (Scheme S1 of the Supporting Information).…”
mentioning
confidence: 95%
“…Processes, such as oxidative, base/acid-catalyzed, and (catalytic) fast pyrolysis, have also been explored for lignin depolymerization . Additionally, aromatic bulk chemicals, such as phenols and aromatics, can be obtained from kraft lignin using reductive processes, like catalytic hydrotreatment. In this communication, we show that a simple mechanochemical pretreatment (viz., ball milling) of kraft lignin before solvent-free hydrotreatment can lead to improved performance (i.e., 15% increase in the recovered oil yield, 15% more alkylphenols, and 33% reduction in solids) compared to unmilled kraft lignin.…”
mentioning
confidence: 99%
See 1 more Smart Citation